Pembuatan Bioplastik Berbasis Pati Sagu Menggunakan Modifikator Asam Sitrat Dengan Microcrystalline Cellulose (Mcc) Sebagai Filler Dan Sorbitol Sebagai Plasticizer - Novriyani, Vivi; Utami, Syelvia Putri; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The use of synthetic plastic in daily life trigger environmental problems. Bioplastic or biodegradable plastic is one of alternative solution to change comercial plastic that can be dangerous to environment because it is difficult to be degraded. One of the potential materials to become the raw materials is sago because of its high starch component. The general purpose of this research is to determine the characteristics of sago-based bioplastic by modified the citric acid, microcrystalline cellulose filler, plasticizer sorbitol. The synthesis method is casting of starch, water, filler and plasticizer with composition of filler is (15-25 % b/b), composition of plasticizer (25–35 % b/b), and composition citric acid (3-9 % b/b). The analysis of bioplastic was tensile strength, elongation, biodegradation,. The most significant factor of all responses was composition of filler microcrystalline cellulose, followed by plastcizer sorbitol and citric acid. The best process condition was bioplastic with composition filler 20 %b/b, plasticizer 30 % b/b, and citric acid 0,95 % b/b with the value was tensile strenght 15.84 MPa, elongation 9,31% and biodegradation 51.65%. Keyword : bioplastic, casting, filler, plasticizer, water uptake